Determinan Produktivitas Tenaga Kerja di Provinsi Sumatera Barat - Nova Afiza Putri; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2025)
In West Sumatra Province, education, health, and wages are the main factors affecting worker productivity. Labor productivity in West Sumatra Province has been inconsistent over the past five years. The purpose of this study is to analyze how education, health, and wages affect labor productivity. The methodology used in this study is panel data regression with a fixed effect model. The results of the analysis show that education has a significant positive effect on labor productivity, health has a non-significant negative effect, and wages have a significant negative effect on labor productivity.